THE LABORATORY-MODELLING COMPLEX FOR RESEARCH of QUALITY INDICATORS Of TELEVISION TYPE OpTiCAL loСation SYSTEM WORK - R. A. Hutsau; A. S. Solonar; S. V. Tsuprik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The structure of a laboratory-modeling complex for researching the quality indicators of algorithms work for detection, measurement, support in optical-location systems is offered, using for this purpose as entrance influence a stream of video of the information of phon and target conditions from the multimedia screen.